Caesalpiniabonducella – A REVIEW ON pharmacological and phytochemical activity of seeds - P. AMUDHA,; N. PUSHPA BHARATHI,; V. VANITHA, (International Journal of Pharma and Bio Sciences, 2016)
Many herbal remedies have been employed in various medical systems for the treatment and management of different diseases. The plant Caesalpinia bonducella has been used in different system of traditional medication for the treatment of diseases and ailments of human beings. The phytochemical screening of seeds of Caesalpinia bonducella revealed the presence of bioactive compounds such as Triterpenoids, Flavonoids, glycosides, saponins, tannins, alkaloids and amino acids. C. bonducella has been reported to have antidiabetic, anti-inflammatory, anti-filarial, anxiolytic, analgesic, antipyretic, immunomodulatory, hypoglycemic, antidiuretic, antiestrogenic, antimicrobial, antifungal, anticonvulsant activity. This review attempts to encompass the available literature on seeds of Caesalpinia bonducella with respect to its pharmacognostic characters, chemical constituents, summary of its various pharmacological activities and traditional uses. Therefore, this information will be helpful to create interest towards the plant and may be useful in developing new formulations.